Pengaruh Motivasi dan Pelatihan Terhadap Kinerja Pegawai Suku Dinas Perizinan Bangunan Jakarta - Desmahadiyanti, Putri Ayu; Hubeis, Aida Vitayala S.; Sunarti, Euis (Jurnal Aplikasi Manajemen, 2015)
This study is conducted on the basis of the broad duty of civil servant as the world develop into advance and competitive stage. Organization is required to acquire, develop and maintain qualified human resources in order to serve community well since the society becomes more critical especially to the policy in which is made by government. Civil servants must have willingness and enthusiasm supported by good competencies to achieve the goals of the organization. Suku Dinas Perizinan Bangunan Jakarta is an organization which provides services in controlling license and feasibility of a building. The purpose of this study is to examine the influence between motivation and training variable on employee performance. Data collection techniques of this study used observation, interview and questionnaire with semantic scale techniques in three regions, namely East Jakarta, North Jakarta and Central Jakarta. Data analysis was performed by multiple linear regression analysis method. The result of this study reveals that there is a collective and significant effect between motivation and training variable on employee performance. In addition, there is a partial and significant effect between motivator indicator of motivation variable, qualification indicator of training variable and education characteristic on employee's performance.